Exploratory Study of Palm Oil Fuel Ash as Partial Cement Replacement in Oil Palm Shell Lightweight Aggregate Concrete - Khairunisa, Muthusamy; Nur Azzimah, Zamri (Maxwell Scientific Organization, 2014)
In Malaysia, issue of environmental pollution resulting from disposal of Palm Oil Fuel Ash (POFA) which is a by-product from palm oil mill has initiated research to incorporate this waste in Oil Palm Shell (OPS) lightweight aggregate concrete production. The current study investigates the effect of palm oil fuel ash content as partial cement replacement towards compressive strength OPS lightweight aggregate concrete. Several OPS lightweight aggregate concrete mixes were produced by replacing various percentage of POFA ranging from 10, 20, 30, 40 and 50%, respectively by weight of cement. All the mixes were cast in form of cubes and then subjected to water curing until the testing date. The compressive strength test is conducted in accordance to BSEN 12390 (2009) at 7 and 28 days. From the results, it was observed that the combination of appropriate POFA content would enhance the compressive strength of OPS lightweight aggregate concrete. Specimen produced using 20% POFA as partial cement replacement exhibit higher value of compressive strength than that of control OPS lightweight aggregate concrete. However, mixes consisting POFA up to 50% is also suitable for structural application.